The reality of political empowerment of Iraqi women and ways to advance them Challenges - and future prospects: Analytical study from the point of political sociology - Ramadan Mohamed, Hamdan (Al-Adab Journal, 2021)
The research aimed to identify the role of Iraqi women in political life after 2003 and to know the extent to which women are able to assume responsibility in the political process and to determine the extent to which circumstances and the current situation affect the woman’s desire for political participation، because the issue of women has become a global issue، and the issue of women's participation in political life is ranked Advanced indicators of the progress of democratic life in societies. The political empowerment of women is related to their legal legitimacy، which is participation in political decision-making processes، elections and voting in any society. We used the descriptive، historical and comparative approach in analyzing the research axes. Women، their participation and empowerment in political action in the new Iraq after 2003.